Pengaruh Motivasi Kerja Dan Interaksi Sosial Terhadap Prestasi Kerja Pegawai Pada Dinas Sosial Kabupaten Lahat - Uchy Cahyani; Marko Ilpiyanto; Titi Hasanah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the effect of work motivation on employee performance at the Lahat Regency Social Service. This study also examined the effect of social interaction on employee performance at the Lahat Regency Social Service. This study also examined the effect of work motivation and social interaction simultaneously on employee performance at the Lahat Regency Social Service. This study used quantitative statistical methods using multiple linear regression, partial regression (t-test), simultaneous regression (f-test), and coefficient of determination. The results showed that work motivation significantly influenced employee performance at the Lahat Regency Social Service. Social interaction significantly influenced employee performance at the Lahat Regency Social Service. Work motivation and social interaction significantly influenced employee performance at the Lahat Regency Social Service.